Pendampingan dan Penyusunan Instrumen Asesmen Kompetensi Minimum untuk Guru IPS di Kabupaten Pacitan - Agus Purnomo; Agung Wiradimadja; Seli Septiana Pratiwi; Nevy Farista Aristin; Aaron Ardery (Jurnal Pemberdayaan Masyarakat, 2023)
The common understanding of the preparation of the Minimum Competency Assessment (AKM) instrument is the main problem for the MGMP IPS of Pacitan Regency as a partner of the Social Sciences Education Study Program, Universitas Negeri Malang. Partners need assistance in the preparation of the AKM IPS instrument. This service aims to improve teacher competence in compiling and providing AKM IPS instruments. The method of implementing community service activities includes the stages of mentoring, monitoring, performance, and impact by the MGMP IPS of Pacitan Regency. Sixty-six teachers attended this activity. The results show that most social studies teachers gave an excellent response of 76%. This can be interpreted that the MGMP IPS teacher understanding the materials and training related to the AKM that the presenters delivered during the activity. Social studies teachers have experienced significant improvements in understanding the AKM of social studies subjects in the current curriculum. So, it can be shown that the program has succeeded in increasing the ability of social studies teachers to prepare for the AKM IPS. The implications of this service are expected to be a guideline in designing the development of a minimum competency assessment instrument so teachers can use it more.